Hansen's disease: social representations of affected people - Raquel Santos Monte; Maria Lúcia Duarte Pereira (Universidade Federal do Ceará, 2015)
Objective: to identify the social representations of leprosy among its carriers. Methods: qualitative study based on the Theory of Social Representations, conducted with 40 subjects with leprosy, divided into two groups (male and female). Data were collected through semi-structured interviews and free observation, submitted to thematic content analysis. Two categories were formulated. Results: it was found different aspects between men and women. Women highlighted issues related to the domestic sphere, care with family and body image; men signaled changes in routine and adaptation to the new condition. Conclusion: the health and especially the nursing model, must seek to understand the daily life of being a leprosy carrier, learning to deal with the differences in each individual, using educational activities that advance toward comprehensive care to the human being.